The impact of foreign investment on balance of payments in Iraq - Mayih Shabeeb Al-Shammari, Alaa Abbas Dakhil, Maiami Salal Sahib Al-shukri, (Opción, 2019)
This examination explores the effect of Foreign Direct Investment (FDI) on the balance of payment. The study is conducted in Iraqi circumstances focusing on the time period of 2005-2017. Johansen-Juselius cointegration technique has been employed to measure the association among variables of interest which are FDI, Current Account Balance (CAB), and Gross Domestic Product (GDP). The results revealed that foreign investment is co-integrated with balance of payment. Furthermore, a positive impact of FDI has been recorded on CAB. In conclusion, as a policy implication, FDI should be taken into account when policymakers are making policies regarding economic development.